An Observation of Nanoparticle‐Assisted Fingering Instability. Issue 1 (20th October 2021) - Has, Chandra; Sunthar, P.
Abstract: Fingering instabilities generally occur in an interface when a lower viscous or higher dense fluid is pushed through another miscible or immiscible fluid of higher viscosity or lower density. Similar fingering phenomena are also seen when hot saline water overlies cold freshwater or two solutes with different diffusivities are employed on two different sides of the interface. In the present study, we report an observation of nanoparticle‐assisted fingering that occurs when a less dense nanofluid lies over a denser liquid in an isothermal condition. Further, we show that the proposed mechanism (i.e., double mass‐diffusive convection) for this kind of fingering works only if nanoparticles are present in the suspending medium but not the microparticles. In the case of microparticles, sedimentation leads to the Rayleigh‐Taylor type of instability.